The Sensitivity of Diagnostic Criteria of Marais S, et al. in Confirmed Childhood Tuberculous Meningitis - Wang, Mao-Shui; Wang, Jun-Li; Liu, Xin-Jie; Zhang, Yan-An (Frontiers in Pediatrics, 2022)
Background To establish the sensitivity of the diagnostic criteria published by Marais and co-workers in 2010 for childhood tuberculous meningitis (TBM), a retrospective study on children with confirmed TBM was conducted. Methods Between January 2006 and December 2019, children consecutively diagnosed with TBM were recruited retrospectively at our center. TBM was defined in cases where any of the following criteria were met: the presence of acid-fast bacilli (AFB) in cerebrospinal fluid (CSF) microscopy, CSF nucleic acid amplification test (NAAT, +) or M.tuberculosis cultured from CSF. The demographic and clinical features of all enrolled patients were recorded including clinical characteristics, CSF findings, cerebral imaging features, and other evidence of TB. Results A total of 30 children with confirmed diagnosis of TBM over an 14-year period were recruited. The mean age of patients was 7.2±5.1 years and 16 (53.3%) were male. The estimated mean diagnostic score was 12.7±2.4. Twenty-three (76.7%; 95% CI: 59.1-88.2%) patients were classified as "probable TBM" according to the Marais criteria and 7 (23.3%; 95% CI: 11.8-40.9%) as "possible TBM.” Further statistical analysis revealed significant differences in CSF scores between probable and possible TBM groups. Other variables reported at a relatively low frequency, such as symptoms and imaging features, made little contribution to TBM diagnosis according to the Marais criteria. Conclusion Childhood TBM could be effectively identified by the criteria defined by Marais et al.. However, further revision is required to ensure that the system is more sensitive and easier to perform in practice.